Aplikasi Beberapa Jenis Pupuk terhadap Pertumbuhan Bibit Kelapa Sawit pad Fase Pre Nursery - Afriani, Siti Rakhmi; Cameron, Rizky (J-Plantasimbiosa, 2024)
Fertilisation in the pre-nursery phase of oil palm plants is very important. Fertilisation can increase the growth of oil palm seedlings, make plants healthy, etc. The purpose of this research is to see the effect of each fertiliser used on several growth parameters of oil palm seedlings. The purpose of this research is to see the effect of each fertiliser used on several growth parameters of oil palm seedlings. the method used in this research is a group randomised design with 5 treatments and 10 replicates. The treatments/fertilisers used in this study were urea fertiliser, P fertiliser, NPK fertiliser, and oragnik cari fertiliser made from active mycorrhiza. The parameters observed were plant height, plant diameter, and leaf length of oil palm seedlings. observations were made every week with a frequency of 3 observations. the results of this study are that each fertiliser has a different effect on each observation parameter and frequency of observation. NPK fertiliser and urea fertiliser were significantly different from other treatments in the first observation of plant height. While in plant diameter, liquid fertiliser made from active mycorrhiza tends to be significantly different from other treatments. In leaf length, the results showed an irregular pattern. However, in the mycorrhizal fertiliser treatment, the number of leaves exceeded 1 of the other treatments.